Educational intervention in Primary Care for the prevention of congenital syphilis - Flaviane Mello Lazarini; Dulce Aparecida Barbosa
ABSTRACT Objectives: to evaluate the efficiency of educational interventions related to the knowledge of health care professionals of Primary Care and to verify the impact on the vertical transmission rates of congenital syphilis. Method: a quasi-experimental study conducted in the city of Londrina, Paraná, between 2013 and 2015. An educational intervention on diagnosis, treatment and notification was carried out with 102 professionals with knowledge measurement before and after the intervention. Incidence and mortality data from congenital syphilis were taken from the system for notifiable diseases (SINAN) and the Mortality Information System (SIM). Excel tabulation and statistical analysis was done in the Statistical Package for Social Sciences, version 2.1. A descriptive and inferential analysis was performed. Results: the mean number of correct responses increased from 53% to 74.3% after the intervention (p < 0.01). The adherence to professional training was 92.6%. There was a significant reduction in the vertical transmission rate of syphilis from 75% in 2013 to 40.2% in 2015. In 2014 and 2015 there were no records of infant mortality from this condition. Conclusion: the educational intervention significantly increased the knowledge of health professionals about syphilis and collaborated to reduce the rate of vertical transmission of the disease.